Professional Responsibility, Consensus, and Conflict: A Survey of Physician Decisions for the Chronically Critically Ill in Neonatal and Pediatric Intensive Care Units*. Issue 9 (September 2017) - Shapiro, Miriam C.; Donohue, Pamela K.; Kudchadkar, Sapna R.; Hutton, Nancy; Boss, Renee D.
Abstract : Objective: To describe neonatologist and pediatric intensivist attitudes and practices relevant to high-stakes decisions for children with chronic critical illness, with particular attention to physician perception of professional duty to seek treatment team consensus and to disclose team conflict. Design: Self-administered online survey. Setting: U.S. neonatal ICUs and PICUs. Subjects: Neonatologists and pediatric intensivists. Interventions: None. Measurements and Main Results: We received 652 responses (333 neonatologists, denominator unknown; 319 of 1, 290 pediatric intensivists). When asked about guiding a decision for tracheostomy in a chronically critically ill infant, only 41.7% of physicians indicated professional responsibility to seek a consensus decision, but 73.3% reported, in practice, that they would seek consensus and make a consensus-based recommendation; the second most common practice (15.5%) was to defer to families without making recommendations. When presented with conflict among the treatment team, 63% of physicians indicated a responsibility to be transparent about the decision-making process and reported matching practices. Neonatologists more frequently reported a responsibility to give decision making fully over to families; intensivists were more likely to seek out consensus among the treatment team. Conclusions: ICU physicians do not agree about their responsibilities when approaching difficult decisions for chronically critically ill children. Although most physicians feel a professional responsibility to provide personal recommendations or defer to families, most physicians report offering consensus recommendations. Nearly all physicians embrace a sense of responsibility to disclose disagreement to families. More research is needed to understand physician responsibilities for making recommendations in the care of chronically critically ill children.